Cardiac Magnetic Resonance in the COVID-19 Outbreak: Essential or Subsidiary? Ressonância Magnética Cardíaca no Surto de COVID-19: Essencial ou Acessória? - Teixeira, Tiago; Pinto, Fernando (Gazeta Médica, 2020)
The COVID-19 pandemic, originated by the new coronavirus SARS-CoV-2, generated high morbidity and mortality. Cardiovascular diseases affect its prognosis, with more and more evidence of myocardial affection by the virus, despite the pathophysiology of it is still unknown. Cardiac magnetic resonance, with its ability to assess tissue characteristics, may, when used in the correct context, provide important information for retrospective diagnosis, essential for the orientation of future serious cases of COVID-19.